"…kazali mu klękać przed martwym wodzem, który poległ w Sandomierzu". W kwestii pochówku mongolskich wojowników oraz ich ofiar w czasie najazdu na Europę - Żerelik, Rościsław (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The paper presents the issue of burials of the victims of the Mongol invasion of Ruthenia, Poland and Hungary and the Mongol warriors in light of the surviving written sources by Christian authors, including i.a. envoys to Karakorum (Jan di Piano Carpini, C. de Bridia) and participants of the burial ceremonies (archdeacon Roger of Torre Maggiore from Great Várad, presently Oradea in Romania, and Kirakos Gandzaketsi), as well as according to uncovered archeological evidence. The author outlined the state of research on this subject and presented his own concepts regarding lack of burials of nomads on the lands they conquered
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne